Neuroinflammation mediates the progression of neonate hypoxia-ischemia brain damage to Alzheimer’s disease: a bioinformatics and experimental study - Zhang, Shengjie; Zhang, Ruqiu; Chen, Zhaoqin; Shao, Zihan; Li, An; Li, Fan; Huang, Fang (Frontiers in Aging Neuroscience, 2025)
BackgroundTraumatic brain injury (TBI) can generally be divided into focal damage and diffuse damage, and neonate Hypoxia-Ischemia Brain Damage (nHIBD) is one of the causes of diffuse damage. Patients with nHIBD are at an increased risk of developing Alzheimer’s disease (AD). However, the shared pathogenesis of patients affected with both neurological disorders has not been fully elucidated.PurposeWe here aim to identify the shared molecular signatures between nHIBD and AD. We used an integrated analysis of the cortex gene expression data, targeting differential expression of genes related to the mechanisms of neurodegeneration and cognitive impairment following traumatic brain injury.MethodsThe gene expression profiles of Alzheimer’s disease (GSE203206) and that of Neonate Hypoxia-Ischemia Brain Damage (GSE23317) were obtained from the Gene Expression Omnibus (GEO) database. After identifying the common differentially expressed genes (DEGs) of Alzheimer’s disease and neonate Hypoxia-Ischemia Brain Damage by limma package analysis, five kinds of analyses were performed on them, namely Gene Ontology (GO) and pathway enrichment analysis, protein–protein interaction network, DEG-transcription factor interactions and DEG-microRNA interactions, protein-drug interactions and protein-disease association analysis, and gene-inflammation association analysis and protein-inflammation association analysis.ResultsIn total, 12 common DEGs were identified including HSPB1, VIM, MVD, TUBB4A, AACS, ANXA6, DIRAS2, RPH3A, CEND1, KALM, THOP1, AREL1. We also identified 11 hub proteins, three central regulatory transcription factors, and three microRNAs encoded by the DEGs. Protein-drug interaction analysis showed that CYC1 and UQCRFS1 are associated with different drugs. Gene-disease association analysis shows Mammary Neoplasms, Neoplasm Metastasis, Schizophrenia, and Brain Ischemia diseases are the most relevant to the hub proteins we identified. Gene-inflammation association analysis shows that the hub gene AREL1 is related to inflammatory response, while the protein-inflammation association analysis shows that the hub proteins AKT1 and MAPK14 are related to inflammatory response.ConclusionThis study provides new insights into the shared molecular mechanisms between AD and nHIBD. These common pathways and hub genes could potentially be used to design therapeutic interventions, reducing the likelihood of Alzheimer’s disease development in survivors of neonatal Hypoxic-Ischemia brain injury.